2014
DOI: 10.1007/978-3-319-09330-7_19
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Support Vector Machine Overfitting on Microarray Data

Abstract: Abstract. Support vector machines (SVM) are a widely used state-of-the-art classifier in molecular diagnostics. However, there is little work done on its overfitting analysis to avoid deceptive diagnostic results. In this work, we investigate the important problem and prove that a SVM classifier would inevitably encounter overfitting for gene expression array data under a standard Gaussian kernel due to the built-in large data variations from DNA amplification mechanism in the transcriptional profiling. We hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…This, however, need not be the case, and other methods, e.g., support vector machines (Vapnik, 2000 ), could be employed for this purpose there. It is worth mentioning, however, that support vector machines might be prone to overfitting (Han, 2014 ) and their training often involves iterative procedures such as sequential quadratic minimization (Platt, 1999 ).…”
Section: Non-iterative Ai Knowledge Transfer Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…This, however, need not be the case, and other methods, e.g., support vector machines (Vapnik, 2000 ), could be employed for this purpose there. It is worth mentioning, however, that support vector machines might be prone to overfitting (Han, 2014 ) and their training often involves iterative procedures such as sequential quadratic minimization (Platt, 1999 ).…”
Section: Non-iterative Ai Knowledge Transfer Frameworkmentioning
confidence: 99%
“…If, for an x generated by an input to AIs, any of i(x) ≥ 0 then report x accordingly (swap labels, report as an error etc.) [22] and their training often involves iterative procedures such as e.g. sequential quadratic minimization [23].…”
Section: Remark 3 Clustering Atmentioning
confidence: 99%
“…The calibration and validation results showed that GA-GMN model has better capability to simulate daily discharge as compared to the GMN and SVM models. SVM performed the worst possibly due to its over-fitting features (Han, 2014). Hence, the GA-GMN model has been chosen to predict the future flow characteristics of the selected river.…”
Section: Resultsmentioning
confidence: 99%
“…We compare the proposed tensor-based classifier OCSTM with vector-based classifier OCSVM on BREAST-CANCER dataset. Similar to the idea of [32,33], to verify the effectiveness dealt with overfitting problem, we use these two evaluation indexes: sensitivity and specificity, where:…”
Section: Experiments On Overfitting Problemmentioning
confidence: 99%